Information technology procurement risk management in fast moving consumer goods industry - Yovita Louwisia, Fabiola Julia; Andika, Aditya (Jurnal Mantik, 2025)
Information Technology procurement is very crucial for companies in the Fast Moving Consumer Goods industry. The rapid product cycles of the industry require continuous launches of new products. This calls for the implementation of modern information technologies in every aspect of the supply chain in order to run operations smoothly and to be competitive. Fast Moving Consumer Goods companies need to ensure that information technologies that are needed for such purpose are procured and implemented. However, there are various risks that arise from IT Procurement in the Fast Moving Consumer Goods industry. To address this matter, this study developed an FMEA-based risk management template that are adjusted to the context of Fast Moving Consumer Goods industry. This study found 27 risks that are related to IT Procurement and develop risk treatment strategies for each of the risks. The risks with the highest RPN scores are mostly related to technological issues and vendor issues. Fast Moving Consumer Goods companies can use this FMEA-based risk management template as a starting point to develop a risk management strategy that are adjusted to their situation and context